Caminhar, fotografar, fabular: entre a cidade e a fotografia - Oliveira, Tatiana Pontes de (2017)
This research addresses the relationship between photography and the city, having as its object of study the contemporary photography produced by walking in the city. The starting point of the research is the question "How does the interaction between the city and the photography happen, considering walking as the procedure used by photographers as a strategy to establish communication with the city?". The main assumptions raised by this question are as follows: a) for having both documentary and fictional features, the photography is an ambivalent means of communication; b) The city is also characterized by ambivalence for being an environment in which interactive experiences and habits are governed by mediative order programs; c) The interaction between the ambivalences of the photographic language and the city enhances the creation of images that make visible the processes of the city and the photographer's imaginary affected by it. In order to verify the hypotheses present in this research, an extensive literature review was carried out to support the empirical analysis of the connections between the city, image and communication, as well as the nature of the photographic language and its ambivalence characterized by documentary and fictional traits. The theoretical foundation follows the goal in each chapter, therefore, in Chapter 01, the image is studied out of a network that connects three authors: Warburg, Benjamin and Flusser. The study of the image concept aims to support the following chapters, in which the relationship between photography and the city is addressed. In Chapter 02, the theoretical foundation links concepts for thinking on the city and its communicative mediative and interactive processes, as well as its dimensions of technosphere and psychosphere, as proposed respectively, by Ferrara and Santos. There is also an investigation on the ambivalence and the specificities of the photographic language taking into account the connections among works by Barthes, Dubois, Kossoy, Soulages and Fontcuberta. Finally, Chapter 03 analyzes the procedure of walking, used by photographers as a poetic strategy to put themselves in touch with the city and seize its manifestations. Having as object of study the photographic works by Daniel Ducci, Felipe Russo, Fernando Cohen and Wesley Barba, the focus of analysis is on how photographers "fable" about the city by creating new possibilities for understanding its impositions and spontaneity proposals, considering the experience of photographing and “fabling” as gestures of resistance